Representasi Kecantikan dalam Iklan Scarlett Whitening Idol Korea TWICE - Adelia Rahma Putri; Arizal Mutahir; Rili Windiasih (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
Globalization and the massive influence of Korean popular culture have shifted the construction of women's beauty standards in Indonesia, including the marketing strategies of local cosmetic products. This study aims to analyze the representation of women's beauty standards and the ideological construction in the local brand advertisement Scarlett Whitening, specifically the "Reveal Your Beauty With TWICE" version. This study employs an interpretative qualitative approach using Roland Barthes' semiotic analysis to deconstruct denotative, connotative, and mythical meanings. The primary data were collected through documentation and observation of the audio-visual elements within the advertisement. The findings reveal that the visual representations in the advertisement emphasize fair, bright, smooth skin, and a youthful appearance as the ideal form of beauty. Connotatively, the advertisement associates product usage with self-confidence, happiness, and social acceptance. At the myth level, the advertisement produces the idea that the universal beauty standard refers to the Korean beauty standard, constructing it as a natural and aspirational condition for the audience to achieve. The presence of K-Pop idol group TWICE as brand ambassadors serves not only as a promotional appeal but also acts as an instrument that produces and reinforces the hegemony of Korean popular culture in shaping the normalization of universal beauty standards in Indonesia.